Monte Carlo simulation variance reduction techniques for photon transport in liquid xenon detectors. Issue 3 (22nd March 2021) - Bruenner, S.; Colijn, A.P.; Decowski, M.P.; Kesber, O.V.
Abstract: Monte Carlo simulations are a crucial tool for the analysis and prediction of various background components in liquid xenon (LXe) detectors. With improving shielding in new experiments, the simulation of external backgrounds, such as induced by gamma rays from detector materials, gets more computationally expensive. We introduce and validate an accelerated Monte Carlo simulation technique for photon transport in liquid xenon detectors. The method simulates photon-induced interactions within a defined geometry and energy range with high statistics while interactions outside of the region of interest are not simulated directly but are taken into account by means of probability weights. For a simulation of gamma-induced backgrounds in an exemplary detector geometry we achieve a three orders of magnitude acceleration compared to a standard simulation of a current ton-scale LXe dark matter experiment.